Incluir la sostenibilidad ambiental en estudios de posgrado (2016)
The article develops methodologically a proposal to include the issue of the sustainability in the master's degree, using the systemic thought approach. This process was supported in the results of the monographs written by students of the Specialization of Environmental Management and the projects of the research line of cleaner production. Two phases are included for the methodological development; the first phase includes review of the research documents of students of the specialization and the second phase does an integration between the content of the research papers and the objectives of the research line. In conclusion, the necessity to make changes on how we look at our daily reality to understand certain issues and fix them to build a fair and just society is the best way to reach the inclusion of environmental sustainability in postgraduate studies.